Silimarin and liver disorders: a literature review (Research, Society and Development, 2023)
Liver disorders are liver -linked diseases. Given the severity of these disorders and the difficulties in establishing a treatment for them, it was decided to propose a new treatment model, using Silimarina, a plant that has been used since ancient times in the cure of various diseases. Given this, the purpose of this research was to discuss the real impact that Silimarina has on liver disorders. For this, this study was based on a descriptive bibliographic review, which was based on scientific papers already published between 2018 and 2022 in Portuguese and specifically dealt with the proposed theme. Data collection took place on database, such as Google Academic, Scielo, PubMed and Lilacs, resulting in 21 scientific works analyzed and released during this study. In the results found, it was clear that silimarin contributes to improving the intestines and the digestive system in general; Modulating the balance of microbiota (by stimulating the proliferation of lactobacillus and bifidobacteria, which would have an important effect of immunomodulatory paper). It still has anti-hepatotoxic action, this means, having liver protection assets and finally helps in the treatment of liver diseases.